Asymmetric synthesis of functionalized 2, 3-dihydrobenzofurans using salicyl N-phosphonyl imines facilitated by group-assisted purification (GAP) chemistry. Issue 47 (23rd November 2021) - Rouh, Hossein; Tang, Yao; Zhang, Sai; Ali, Ahmed I. M.; Unruh, Daniel; Surowiec, Kazimierz; Li, Guigen
Abstract : A new asymmetric method for the synthesis of highly functionalized 2, 3-dihydrobenzofuranes in good to high yields and excellent diastereoselectivity via group-assisted purification (GAP) chemistry. Abstract : In this work, we present a strategy for the preparation of functionalized 2, 3-dihydrobenzofuran derivatives via the Cs2 CO3 -catalyzed domino annulation of enantiopure chiral salicyl N -phosphonyl imines with bromo malonates, which offers an avenue for the construction of 2, 3-dihydrobenzofurans. Nineteen examples were synthesized in impressive chemical yields and diastereoselectivity. The products were purified simply by washing the crude mixtures with hexanes following group-assisted purification chemistry/technology to bypass traditional separation methods which often result in a loss of product. The absolute configuration was unambiguously assigned by X-ray structural analysis.